A Flask based Application for Recommending the Similar Kind of Dresses - B Nair, Reshma; Susila, N.; Priya K, Ranjeetha; Anand, Sruthi (International Journal of Engineering and Technology, 2018)
The growth of online social networks and the amount of information shared through it are immense in the recent years. It provides information in all fields such as education, sports, fashion, etc and also updates us with all the latest news that is happening around the world. Some of the popular social media sites are Facebook, Twitter, Instagram and it has become a platform for people to easily communicate and share information.Â Nowadays business people use social media as their means for communication. Fashion industry is one of the businesses which frequently changes and the social media is considered to be as the cheapest and easiest means to communicate. Hence an application is created which obtains the photos of the user from their facebook account and suggests the similar kind of dresses based on their collection of dresses. Â